A new species of Lepanthopsis (Orchidaceae, Pleurothallidinae) from Peru - Rykaczewski, Max; Baranow, Przemysław; Kolanowska, Marta (Phytotaxa, 2017)
A new species of Lepanthopsis is described and illustrated based on Peruvian material. Lepanthopsis bennettii is similar to L. dewildei from which it differs by long-connate lateral sepals, broadly ovate dorsal sepal, large lip basal lobes and petals form. Phylogenetic placement of the new species as well as identification key and comparative morphology of all known representatives of Lepanthopsis with single-flowered inflorescence are presented.